STRATEGI PENGEMBANGAN EKONOMI ISLAM DI LEMBAGA KEUANGAN SYARI`AH "DINAR GROUP" - , Zeni Luthfiyah (PARENTAL, 2014)
Abstract Economic systemof Shariais consideredto havea specialmarketsegmentandpromising, namelyMuslimswhoconstitutethe majority ofthe Indonesian population. This systemwillbeone of theefforts to realizethe ideals ofcivil society, althoughstillalwaysappearconceptualdebateabouttechnicalimplementation, marketing of products, as well asinterms of reachingthe positionineconomic policy at the state level. This studyintends toexposeaboutways thatdothe practitionersof Islamiceconomicsinthe GroupDinarpreachIslamiceconomic systemandits institutionsas well as effortsto buildresiliencein the face ofchallengesandconstraintsthat accompany it. especially with regard tothe pattern ofrelationshipcoaching is donebythe managementgroupof thebranches, and thestrategies usedin the face ofcompetitionin the same sectorincludingproduct adaptationservices to the needsof customersinthe environment. Keywords: Economic system of sharia, Strategy, Dinar Group